The Role of Culture Management in MSC Subsidiaries; Empirical Case Study of Joy Mining Machinery Company - Suchoronczak, Marta (2007)
This paper looks at the concept of national cultures and their significance for shaping framework of multinational companies. It reviews the prominent literature in the field of culture management and cluster approach attaching a lot of weight to Hofstede's work. Then employing his questionnaire it examines differences between four national cultures working under the management of the same company: Joy Mining Machinery. The national cultures, which undergo scrutiny, are: Poland, China, United Kingdom and America. The results obtained are analysed by means of four cultural dimensions: power distance, uncertainty avoidance, individualism and masculinity, and juxtaposed with Hofstede's scores. The comparison of the new outcomes with the originals provides foundation for descriptive analysis of emerging patterns and trends among respondents. Although low response rate and small sample size of the research affect the credibility of the outcomes the findings of this study suggest tendency of cultural convergence among the examined countries.